Clinical and muscle biopsy findings in Norwegian paediatric patients with limb girdle muscular dystrophy 2I. (10th February 2014) - Rasmussen, Magnhild; Scheie, David; Breivik, Noralv; Mork, Marit; Lindal, Sigurd
Abstract Aim To describe patients diagnosed with limb girdle muscular dystrophy 2I (LGMD2I) in our paediatric departments between 2004 and 2012. Methods The hospital charts of 17 patients presenting for evaluation at a mean age of 7.8 years (range 1–13 years) were retrospectively reviewed. Results With one exception, all patients were homozygous for the common mutation c.826C>A in the FKRP gene. Three patients experienced transient pronounced weakness as toddlers. Fatigue and muscle pain were most prominent, weakness less so, in children presenting at an older age. The degree of severity varied substantially. In certain cases, increased creatine kinase was an incidental finding. All walked independently by 18 months. When last evaluated at a mean age of 14.3 years (range 3.5–18 years), five patients were part‐time wheelchair users. One patient was then treated for a cardiomyopathy. Creatine kinase was consistently increased, except presymptomatic in one patient. Muscle biopsies showed focal acute and chronic myopathic changes and pathological expression of α‐dystroglycan. No consistent relationship between clinical function and the degree of morphological pathology was found. Conclusion LGMD2I is a relevant differential diagnosis when creatine kinase is increased in children presenting with fatigue, muscle pain and sometimes weakness.